Milling as a method of surface pre-treatment of steel for adhesive bonding. Issue 23 (1st December 2016) - Rudawska, Anna; Reszka, Magdalena; Warda, Tomasz; Miturska, Izabela; Szabelski, Jakub; Stančeková, Dana; Skoczylas, Agnieszka
Abstract: The paper analyses the impact of mechanical milling pre-treatment parameters on adhesive joint strength. Comparison of surface roughness of adherends after milling and its effect on adhesive joint strength is analysed in strength tests. The tests were performed on C45 structural steel specimens, which were subjected to machining at different parameters, with two types of milling cutters. Adherends were degreased prior to adhesive joining. Two types of end mills used in tests were NFPaφ20 high-speed steel cutter and R390-020B20-11L indexable milling cutter. The machining was carried out at three cutting speeds: 0.05, 0.15 and 0.30 mm/tooth. Adherends were joined with an adhesive composition of Epidian 57 epoxy resin and Z-1 curing agent.